Pengaruh Disiplin Kerja, Budaya Organisasi, Komitmen Kerja dan Kompensasi terhadap Kinerja Karyawan Pada PT. Sumber Batu Persada di Desa Nyampir, Kecamatan Bumi Agung - Ismaya, Lulut; Japlani, Ardiansyah (Universitas Muhammadiyah Metro, 2021)
This study aims to analyze the influence of Work Discipline, Organizational Culture, Work Commitment, and Compensation on employee performance. This type of research is a quantitative study with a population of 35 employees who are registered at PT. Sumber Batu Persada In Nyampir Village, Bumi Agung Subdistrict, East Lampung, only 33 samples were used that fit the predetermined criteria. The data used is secondary data distribution of questionnaires in the form of a list of questions with several alternative answers for respondents. The statistical test used to test the hypothesis is multiple linear regression analysis and is tested using the statistical packages for the social science (SPSS) program version 21.